Impact of Renewable and Non-Renewable Energy Resources on CO2 Emission: Empirical Evidence from SAARC - Akbar, Ahsan; Gul, Azeem; Sohail, Mariam; Hedvicakova, Martina; Haider, Syed Arslan; Ahmad, Sareer; Iqbal, Samra (International Journal of Energy Economics and Policy, 2024)
When assessing sustainability performance, researchers often ignore the implications of combining energy, economic, and environmental factors. To address this void, we assess the consequence of energy dis-aggregation proceeding carbon emissions in SAARC nations. The majority of energy resources are renewable and non-renewable, which contributes to a rise in carbon dioxide emissions. This study aims to provide a thorough understanding of the energy utilization dioxide emissions nexus. The panel data sets covering the period 1971-2020 for the SAARC nations have been used for analysis. The data set was used to assess the effect of renewable and non-renewable energy consumption on emissions of carbon dioxide by factoring in other CO2-producing variables such as urbanization, primary and secondary education, globalization, and economic development. Panel Fully Modified Ordinary Least Squares (FMOLS) was used to examine the connection. According to research comparing the impact of renewable and non-renewable energy consumption upon Carbon dioxide emission, whereas non-renewable energy consumption increases CO2 emissions, renewable energy consumption decreases them. Urbanization, globalization, primary education, and economic growth increase carbon emissions, while secondary education contributes to environmental quality improvement via CO2 reduction. Therefore, increasing the usage of renewable energy and enhancing awareness through higher education may help SAARC nations to reduce pollution emissions.